Left Atrial Size and Function in Hypertrophic Cardiomyopathy Patients and Risk of New-Onset Atrial Fibrillation. (February 2017) - Debonnaire, Philippe; Joyce, Emer; Hiemstra, Yasmine; Mertens, Bart J.; Atsma, Douwe E.; Schalij, Martin J.; Bax, Jeroen J.; Delgado, Victoria; Marsan, Nina Ajmone
Abstract : Background—: The value of left atrial (LA) diameter, volume, and strain to risk stratify hypertrophic cardiomyopathy patients for new-onset atrial fibrillation (AF) was explored. Methods and Results—: A total of 242 hypertrophic cardiomyopathy patients without AF history were evaluated by (speckle-tracking) echocardiography. During mean follow-up of 4.8±3.7 years, 41 patients (17%) developed new-onset AF. Multivariable analysis showed LA volume (≥37 mL/m 2 ; hazard ratio, 2.68; 95% confidence interval, 1.30–5.54; P =0.008) and LA strain (⩽23.4%; hazard ratio, 3.22; 95% confidence interval, 1.50–6.88; P =0.003), but not LA diameter (≥45 mm; hazard ratio, 1.67; 95% confidence interval, 0.84–3.32; P =0.145), as independent AF correlates. Importantly, 59% (n=24) of AF events occurred despite a baseline LA diameter <45 mm, observed in 185 patients. In this patient subset, LA strain (area under the curve 0.73) and LA volume (area under the curve 0.83) showed good predictive value for new-onset AF. Furthermore, patients with LA volume <37 versus ≥37 mL/m 2 and LA strain >23.4% versus ⩽23.4% had superior 5-year AF-free survival of 93% versus 80% ( P =0.003) and 98% versus 74% ( P =0.002), respectively. Importantly, LA volume <37 mL/m 2 and strain >23.4% yielded high negative predictive value (93% and 98%, respectively) for new-onset AF. Likelihood ratio test indicated incremental value of LA volume assessment ( P =0.011) on top of LA diameter to predict new-onset AF in hypertrophic cardiomyopathy patients with LA diameter <45 mm, which tended to increase further by addition of LA strain ( P =0.126). Conclusions—: LA diameter, volume, and strain all relate to new-onset AF in hypertrophic cardiomyopathy patients. In patients with normal LA size, however, both LA volume and strain further refine risk stratification for new-onset AF. Abstract : Supplemental Digital Content is available in the text.